2018
DOI: 10.1080/03630269.2018.1488723
|View full text |Cite
|
Sign up to set email alerts
|

Development of Visual Detection of α-Thalassemia-1 (the – –SEA Deletion) Using pH-Sensitive Loop-Mediated Isothermal Amplification

Abstract: Detection of α-thalassemia-1 (α-thal-1) carriers provides valuable insight for genetic consulting in prevention and control programs for couples who are at risk of conceiving a fetus with severe thalassemia, both Hb Bart's hydrops fetalis and hemolytic Hb H disease. The traditional method is complicated, time-consuming and requires high instrument cost and expertise. Loop-mediated isothermal amplification (LAMP) based on pH-sensitive dye technology, shows all the characteristics required of a real-time analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…10 A previous study detected the -SEA (Southeast Asian) deletion, and IVSII-I G>A mutation indicating thalassemia using LAMP assays. 11,12 Thus, new LAMP methods capable of detecting thalassemia could be alternative methods to other techniques, and could be used in primary hospitals and rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…10 A previous study detected the -SEA (Southeast Asian) deletion, and IVSII-I G>A mutation indicating thalassemia using LAMP assays. 11,12 Thus, new LAMP methods capable of detecting thalassemia could be alternative methods to other techniques, and could be used in primary hospitals and rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…This association showed high specificity in detecting abnormal α-globin genes. Moreover, there is no cross-reactivity with α 4.2 and α 3.7 deletion 50 .…”
Section: Loop-mediated Isothermal Amplificationmentioning
confidence: 90%
“…Loop-mediated isothermal amplification (LAMP) is a novel method for nucleic acid amplification in molecular diagnostics as it is highly sensitive, specific, rapid, accurate, and cost-effective 50 . This technique requires four to six primers for six regions on the targeted gene, and the primer sets are specific to the target areas 51 .…”
Section: Loop-mediated Isothermal Amplificationmentioning
confidence: 99%
“…We successfully designed two sets of LAMP primers, whereas the previous study only reported one set of primer used in the detection of two α genes deletion --SEA type [11]. The similarities in the sequence of current primers (F3D and B3D) with the previously reported primer [11] may be due to its design using the same web-based free software, however, different DNA templates were used.…”
Section: Discussionmentioning
confidence: 99%
“…LAMP meets all of the criteria for an ideal diagnostic test because of its sensitivity, specificity, low cost, simplicity, speed, adaptability to all kinds of climatic changes, and the availability of instruments used, as suggested by the World Health Organization [10] in a report of their findings. The previous study reported the application of LAMP for the detection of α 0 thalassemia carrier --SEA type using different intercalating dyes such as pH-sensitive dyes [11]. Based on the advantage of using HNB as a DNA intercalating dye addition before amplification and colorimetric using naked eye detection [12], we tried to develop the simplest method, HNB-LAMP, for the detection of the α 0 thalassemia carrier --SEA type.…”
Section: Introductionmentioning
confidence: 99%